Avaliação de diferentes ativadores alcalinos nas propriedades do cimento supersulfatado (CSS) - Schuster, Geciele Caroline (2019)
In order to reduce the environmental impacts on the production of Portland cement (CP), studies have been conducted with the objective of obtaining sustainable cement, in which the lower energy consumption and raw materials are highlighted. One such cement is supersulfated (CSS), which uses in its composition a by-product of the steelmaking industry, pig iron slag. In the present work, to obtain the CSS pastes, proportions of 85% of pig iron slag, 15% of a source of calcium sulfate (anhydrite) and small concentrations of alkaline activator were used. By adding slag to anhydrite, together with alkaline activator, CSS formation / hydration is observed with the emergence of its main products, ettringite and hydrated calcium silicate (CSH). Etringite is responsible for the development of strength at recent ages, from a few hours to 7 days of hydration, and CSH at later ages. The role of the alkaline activator in the formation of SSC is of fundamental importance, since, by increasing the reaction pH, it promotes the dissolution of slag, contributing to the formation of hydrated products. This study aims to analyze the effect of different alkaline activators (NaOH, KOH, Ca (OH) 2 and CPV) at varying concentrations on the performance of supersulfated cement. To follow up this work, analyzes were performed with 7, 28 and 90 days of X-ray diffraction, exploratory calorimetry and scanning electron microscopy (90 days only), as well as tests of compressive strength, pH monitoring and conduction calorimetry. 168 hours. The activators that obtained the best compressive strength results at 90 days were NaOH and KOH. In the analyzes carried out of pH it is possible to observe that the variation of the concentration of the activator used influences the pH, which tends to have consequences in the hydrated products as the ettringita, for example, and consequently the reduction of the compressive strength.